Comparative analysis of medicinal plants Scutellaria baicalensis and common adulterants based on chloroplast genome sequencing - Zhen Li; Baozhong Duan; Zhongyu Zhou; Hui Fang; Meihua Yang; Conglong Xia; Ying Zhou; Jing Wang (BMC Genomics, 2024)
Abstract Background Scutellaria baicalensis Georgi has been extensively used as a medicinal herb in China for over 2000 years. They may be intentionally or inadvertently substituted or blended with comparable species in the local market, threatening clinical medication safety. Molecular markers are effective tools to prevent misidentification and eliminate doping and falsification among Scutellaria plants. This study screened four highly variable regions to identify Scutellaria and its adulterants. In addition, a phylogenetic analysis was performed using the complete cp genome combined with published Scutellaria species samples. Moreover, a comparative analysis of the cp genomes was conducted to investigate the cp genome evolution of S. baicalensis. Results The complete cp genome of five species of Scutellaria was sequenced for the first time, and four previously published Scutellaria species were re-sequenced. They all exhibited a conserved quadripartite structure in their cp genomes, including two distinct regions, namely a small and large single copy region, respectively, and two inverted repeats encompassing the majority of ribosomal RNA genes. Furthermore, the nine species exhibited high conservation from aspects of the genome structure, codon usage, repeat sequences, and gene content. Four highly variable regions (matK-rps16, ndhC-trnV-UAC, psbE-petL, and rps16-trnQ-UUG) may function as potential molecular markers for differentiating S. baicalensis from its adulterants. Additionally, the monophyly of Scutellaria was ascertained and could be reclassified into two subgenera, subgenus Anaspis and subgenus Scutellaria, as evidenced by the phylogenetic analyses on sequences of cp genome and shared protein-coding sequences. According to the molecular clock analysis, it has been inferred that the divergence of Scutellaria occurred at approximately 4.0 Mya during the Pliocene Epoch. Conclusion Our study provides an invaluable theoretical basis for further Scutellaria species identification, phylogenetics, and evolution analysis.